Complete mitochondrial genome of the river stingray Potamotrygon orbignyi (Myliobatiformes: Potamotrygonidae). Issue 2 (3rd July 2019) - Ory, David; Cuenot, Yves; Vigouroux, Régis; Covain, Raphaël; Brosse, Sébastien; Murienne, Jérôme
Abstract: The river stingray Potamotrygon orbignyi is a carnivorous bottom feeder that is widespread in the Amazonian region. We here assemble the 17, 449 bp complete mitochondrial genome of the species, showing a typical gene arrangement as for related Potamotrygonidae. The analysis of the COI gene confirmed the identification of the specimen as P. orbignyi . A phylogenetic analysis of all Potamotrygonidae complete mitochondrial genomes highlights the close relationship between P. orbignyi and P. motoro .